Measuring changes in preferences and perception due to the entry of a new brand with choice data - Lutz Hildebrandt; Lea Kalweit (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
Context effects can have a major influence on brand choice behavior after the introduction of a new product. Based on behavioral literature, several hypotheses about the effects of a new brand on perception, preferences and choice behavior can be derived, but studies with real choice data are still lacking. We employ an internal market structure analysis to measure context effects caused by a new product in scanner panel data, and to discriminate between alternative theoretical explanations. An empirical investigation reveals strong support for categorization effects and changes in perception, which affect customers in two out of five segments.
Keywords: M31; C23; C51; 330; Context effects; categorization; brand choice models; new brand introduction; Konsumentenverhalten; Markenartikel; Innovation; Wahrnehmung; Sortiment; USA